KHANDURI WEU IN THE CONTEXT OF CULTURAL TRADITION AND ISLAMIC LAW IN THE VILLAGE OF LAMPANAH LEUNGAH ACEH BESAR - Yus, Sulhan; Muhammad Ash Shiddqi; Zubaidah; Suraiya; Nurul Izzah; Syed Najihuddin Syed Hassan (Balai Penelitian dan Pengembangan Agama Jakarta, 2025)
The Khanduri Weu ritual is a pre-Islamic ritual that is still practiced by the Muslim community in Lampanah Leungah to this day, with only slight changes to its purpose. This study aims to examine the Khanduri Weu ritual from the perspective of culture and Islamic law in Aceh. This study uses a qualitative approach with ethnographic research. Data was collected through unstructured interviews, observation, and documentation. The results of the study show that, from a cultural perspective, the Khanduri Weu ritual can be seen from the variety of special foods served and the tradition of free-range livestock, which demonstrate the strong cultural characteristics of Aceh Besar. It also shows the strong social identity of the Lampanah Leungah community in maintaining this ritual as part of their lives. From the perspective of Islamic law in Aceh, Khanduri Weu demonstrates Islamic values in strengthening social relationships and solidarity. In addition, it strengthens the relationship with Allah through charity and communal prayer. The results of this study contribute to enriching the literature on local Islamic rituals in Indonesia and the Southeast Asian region in general.